The importance of poetry and imagination - Costa, Maria Cristina Castilho (Comunicação & Educação, 2008)
The author remembers her past of young reader interested in literary works underestimated by school and the embarrassment that has marked her youth because of Gone with the Wind, classic example of book censored by the old school and homonymous of the motion picture acclaimed until nowadays. Thus, she commemorates with readers the change of times and how education watches with good eyes the interest of students by media, reading novels and almost all sorts of literature. She emphasizes how this revolution approaches students to teachers and teaching to what effectively concerns and attracts students.